The Paradox of the Pavements – How the Cultural Value of Limestone Pavements Resulted in Widespread Damage to These Landforms Across Northern Britain and What Has Been Done about it - Murphy Phillip (Geoconservation Research)
Limestone pavements, formed in part as a result of glacial scour, are highly valued parts of the landscape of northern Britain. They have been quarried extensively for use in both gardening and for landscaping in urban recreational spaces. Legal protection was provided in the 1980s and extraction has since been halted in England. This has been a geoconservation success story but there are ongoing concerns that damage may have been displaced to other areas of the British Isles.